Pengaruh komposisi media terhadap pertumbuhan dan kualitas lingkungan kultur Pavlova sp. - Iwamony, Johanes L.; Pattinasarany, Maureen M.; Pattipeiluhu, Shelly M.; Jamal, Endang (Indonesian Journal of Sustainable Aquaculture, 2024)
To optimise the production of microalgae culture, manipulation of media culture composition is one of the efforts. This study aimed to compare the growth of microalgae Pavlova sp. and the environmental culture conditions between different media compositions. Pavlova sp. was cultured for nine days using three different media compositions: A, B, and C. Cell density was counted daily. The concentration of ammonia, nitrate, and phosphate, as well as total Vibrio and total bacteria, were measured during the culture period on the 3rd, 6th, and 9th day. The result showed that the highest cell density was found in C media (5,08 x 106 cells/ml) followed by B media (4,58 x 106 cells/ml) and A media (4,46 x 106 cells/ml), but statistically, there was not significantly different growth rate between those media (P=0.83 >0.05). Phosphate and nitrate concentrations decreased in all media, but ammonia increased. The total count of bacteria and Vibrio sp. on C media was lower than on A and B media. This finding indicated that the composition of C media was more suitable for the growth and culture environmental condition of Pavlova sp. culture at a semi-massal scale.